ANALISIS FAKTOR PENYEBAB DAN DAMPAK PERNIKAHAN DINI DI DESA WAIPAAR, KECAMATAN TALIBURA - Yoseph Darius Purnama Rangga; Elisabeth Vicha Evarista Maring; Theresia Yulyani; Fransiska Anyelis; Aloysius Aryanto Moa Panga; Aloysia Wihelmina Iry; Muhammad Syahrul Ramadhan Syabanda; Gabriela Triska Ta’a; Elisabeth Susanti (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
A wedding is a marriage vow ceremony carried out by two people with the intention of building a household which is formalized according to custom, religion and law. The aim of this research is to determine the number of couples who marry at an early age in Waipaar Village. The method in this research is quantitative research using observation and interview data collection techniques. The sample from this study consisted of 100 couples consisting of 50 couples who married young. The implementation method is in the form of community service activities using educational strategies. Interview results from 10 couples representing 50 couples said that their parents were not able to afford education so they made the decision to marry at an early age, because they thought that marrying at an early age could ease the burden on their parents. And also encouraging them to have their own home after marriage is to live more independently and can bring comfort and a sense of calm.